PATIENTS SATISFACTION ABOUT HEALTH CARE DELIVERY IN OUT-PATIENTS DEPARTMENT OF COMBINED MILITARY HOSPITAL RAWALPINDI - Sardar, Tahir; Khan, Iqbal Ahmad; Khan, Muhammed Alamgir (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine patient’s level of satisfaction and factors leading to dissatisfaction in selected patientsgroup with health care delivery in outpatients department of CMH Rawalpindi.Study Design: Cross sectional study.Place and Duration of Study: Out Patients Department of Combined Military Hospital Rawalpindi, from Sep2013 to Aug 2015.Methodology: Before data collection, written informed consent was taken from all the participants. The studypopulation comprised of armed forces personnel and their families. Patients, including both, males and females, coming to the outpatient department of Combined Military Hospital Rawalpindi were included in the study through consecutive sampling.Results: Results revealed that only 30% were satisfied. 67% patients were satisfied with the facilities in reception and 70% were satisfied with cleanliness in waiting area. A relatively low level of satisfaction with dealing of nursing assistant was recorded while very high percentage of satisfaction with performance of doctor i.e. 91%, examination done by doctor 91% and information provided by doctor 93% was recorded.90% patients reported high level of satisfaction with medicines provided.95.33% patients were satisfied with lab tests being done in hospital.Conclusion: Assessing satisfaction of patients is a simple and cost effective way for assessment of hospitalservices. Most of the patients were contented with services delivered in OPD and showed their trust in doctors,medicines provided and lab facilities offered. Majority were willing to revisit the hospital if required.